Socio-Psychological Characteristics of Family Relations - Azizova Iroda Furqatovna (Lembaga Yasin AlSys, 2026)
Against the backdrop of persistent pressure and violence against women within family relations, this article analyzes the socio-psychological causes and consequences of such violence and examines mechanisms for its prevention. The study adopts a socio-psychological and conceptual approach to systematize factors embedded in family interaction, power dynamics, and socialization processes, and to clarify how these factors shape both the experience and outcomes of pressure and violence against women. The analysis considers the impact of violence on women’s psychological well-being and social functioning, and identifies key directions for preventive action within the family and broader social environment. The findings highlight the crucial role of psychological prevention, social support systems, and moral-educational approaches in reducing the risk of violence, mitigating its consequences, and strengthening women’s socio-psychological protection. The article concludes that effective prevention of violence against women in family relations requires the coordinated development of socio-psychological prevention strategies, supportive social infrastructures, and value-oriented educational initiatives. In doing so, it contributes to a more comprehensive understanding of family-based gender violence and offers a prevention-oriented perspective that can guide future research and practice.